Wound Dehiscence and Device Migration after Subconjunctival Bevacizumab Injection with Ahmed Glaucoma Valve Implantation - Miraftabi, Arezoo (J Ophthalmic Vis Res, 2016)
PURPOSE: To report a complication pertaining to subconjunctival bevacizumab injection as an adjunct to Ahmed Glaucoma Valve (AGV) implantation. CASE REPORT: A 54-year-old woman with history of complicated cataract surgery was referred for advanced intractable glaucoma. AGV implantation with adjunctive subconjunctival bevacizumab (1.25 mg) was performed with satisfactory results during the first postoperative week. However, 10 days after surgery, she developed wound dehiscence and tube exposure. The second case was a 33-year-old man with history of congenital glaucoma and uncontrolled IOP who developed AGV exposure and wound dehiscence after surgery. In both cases, for prevention of endophthalmitis and corneal damage by the unstable tube, the shunt was removed and the conjunctiva was re-sutured. CONCLUSION: The potential adverse effect of subconjunctival bevacizumab injection on wound healing should be considered in AGV surgery.